2016
DOI: 10.1038/ncomms10410
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal microbiome is related to lifetime antibiotic use in Finnish pre-school children

Abstract: Early-life antibiotic use is associated with increased risk for metabolic and immunological diseases, and mouse studies indicate a causal role of the disrupted microbiome. However, little is known about the impacts of antibiotics on the developing microbiome of children. Here we use phylogenetics, metagenomics and individual antibiotic purchase records to show that macrolide use in 2–7 year-old Finnish children (N=142; sampled at two time points) is associated with a long-lasting shift in microbiota compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
528
6
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 571 publications
(574 citation statements)
references
References 60 publications
33
528
6
7
Order By: Relevance
“…Another, published in 2016 by Finnish researchers, reported that antibiotic use, and macrolide use in particular, was associated with a long-term reduction in microbial richness [15]. Antibiotic-treated children still did not reach the level of the control samples even 12-24 months after the course.…”
Section: Antibiotic Exposures Impair the Diversity And Stability Of Gmentioning
confidence: 99%
See 2 more Smart Citations
“…Another, published in 2016 by Finnish researchers, reported that antibiotic use, and macrolide use in particular, was associated with a long-term reduction in microbial richness [15]. Antibiotic-treated children still did not reach the level of the control samples even 12-24 months after the course.…”
Section: Antibiotic Exposures Impair the Diversity And Stability Of Gmentioning
confidence: 99%
“…Delayed microbiota maturation, as defined in healthy children, mirrors physiological disturbances in the host and occurs in mice exposed to antibiotics [20,21]. investigated 142 Finnish children aged 2-7 years (median age 5 years) who attended the same day-care centers at the time of the study to understand how the use of specific antibiotics can affect the intestinal microbiota in different ways [15]. The 16S rRNA sequencing data of the bacterial community obtained from the fecal samples showed that children's gut microbial community composition can clearly reflect the use of antibiotics and antibiotic use will slow down the development of microbial community [22,23].…”
Section: Antibiotic Use Disrupts Structure Of Gut Flora and Metabolicmentioning
confidence: 99%
See 1 more Smart Citation
“…Such data are needed to screen for antibiotics that hit the pathogen, but not so much the commensals which are responsible for colonization resistance. Indeed, a prospective study in Finnish children showed that macrolide antibiotics caused a long‐lasting shift in microbiota composition and metabolism, while penicillins left a much weaker mark (Korpela et al ., 2016a). The above‐mentioned gut microbiome dysbiosis in CDI is a lively reminder of the extent of biome disturbance by an intense antibiotic treatment schedule and its clinical consequences.…”
Section: Eliminating Undesired Bacteria From the Gut Microbiomementioning
confidence: 99%
“…compared to nowadays with our lives being exposed to mass production of processed foods, often enriched by additives and taste enhancers as well as antibiotics and/or being genetically modified. The question arises whether all these modifications in corroboration have had an impact on the animal and human intestinal microbiome and changes in metabolism [7][8][9].…”
mentioning
confidence: 99%